(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is dedicated to the study of early detection and effective treatment methods for cervical diseases associated with human papillomavirus (HPV), a common and serious health threat among women of reproductive age. The research thoroughly analyzes the etiology of HPV infection, its transmission routes, and its association with cervical dysplasia and cancer. Additionally, the advantages of screening, colposcopy, cytological, and molecular diagnostic methods are reviewed. The study also highlights the importance of modern treatment approaches such as cryotherapy, LEEP, immunotherapy, and vaccination. Based on the results of the research, advanced strategies are proposed to preserve the health of women of reproductive age, with particular emphasis on preventive measures.